Options for the Development of Noninvasive Glucose Monitoring: Is Nanotechnology an Option to Break the Boundaries?. (May 2016) - Thomas, Andreas; Heinemann, Lutz; Ramírez, Araceli; Zehe, Alfred
Nowadays nanotechnology has many applications in products used in various areas of daily life; however, this technology has also an option in modern medicine and pharmacy. Therefore, this technology is also an attractive option for the field of diagnosis and treatment of diabetes. Many people with diabetes measure their blood glucose levels regularly to determine the insulin dose. Ideally glucose values would be measured noninvasively (NI). However, none of all the NI approaches studied in the past decades enabled reliable NI measurements under all daily life conditions. Particularly an unfavorable signal-to-noise ratio turned out to be problematic. Based on the known physical possibilities for NI glucose monitoring the focus of this review is on nanotechnology approaches. Functional prototypes exist for some of these that showed promising results under defined laboratory conditions, indicating a good sensitivity and selectivity for glucose. On the second hand is to optimize the technological process of manufacturing. In view of the rapid progress in micro- and nanoelectronics hopefully NI glucose monitoring systems can be developed in the near future.